2018
DOI: 10.1097/bpo.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

What’s New in Pediatric Hip?

Abstract: Level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…As indications for hip arthroscopy have evolved to include pediatric hip conditions, there has been a lack of studies in the literature investigating the safety of its use. 10,13,15 Neurapraxia or nerve injury is a potential complication from traction in hip arthroscopy, as documented in the literature. 16 While this complication can still occur, it was more frequent during the early days of hip arthroscopy when traction times were longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indications for hip arthroscopy have evolved to include pediatric hip conditions, there has been a lack of studies in the literature investigating the safety of its use. 10,13,15 Neurapraxia or nerve injury is a potential complication from traction in hip arthroscopy, as documented in the literature. 16 While this complication can still occur, it was more frequent during the early days of hip arthroscopy when traction times were longer.…”
Section: Discussionmentioning
confidence: 99%
“…16 Few studies have examined the frequency and risk for iatrogenic neurologic complications during hip arthroscopy in the pediatric population, despite the fact that its use has expanded to include treatment for sequelae of developmental dysplasia of the hip, Legg-Calve-Perthes disease, slipped capital femoral epiphysis (SCFE), epiphyseal dysplasia, femoral acetabular dysplasia, septic arthritis, and trauma, as the alternative for these pathologies may include open surgical hip dislocation. 10,13,15 Although the rate of pediatric pudendal nerve injury has been noted to range from \1% to 9% after hip arthroscopy for labral debridement in structurally normal hips, 5,10,14 no studies have either examined the rate of neuromonitoring changes of the sciatic nerve due to traction or assessed the risk factors for sciatic nerve injury in the pediatric population.…”
mentioning
confidence: 99%
“…В ведущих зарубежных изданиях традиционно публикуются аналитические статьи, содержащие обзор результатов текущих исследований по различным направлениям нашей специальности [5][6][7][8], и обсуждаются способы улучшения контроля качества научной продукции [9][10][11]. однако в отечественной травматологии и ортопедии аналитических обзоров соответствующего профиля нам найти не удалось.…”
Section: таблица 3 сведения о характере и уровнях кандидатских и доктunclassified
“…The complication rate after SCFE treatment is difficult to assess [18], given the lack of standardized clinical data reporting and multicentre studies. A recent study reported an overall 29.4% AVN rate in a cohort of patients with stable SCFE treated with modified Dunn procedure [2], compared to a cohort of patients with unstable slips, who experienced a 6% AVN rate [19]. A 4% incidence of anterolateral hip instability was also found after modified Dunn procedure [20].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis of the hip may be the end result of congenital or acquired hip conditions occurred during the juvenile age [1]. Developmental dysplasia of the hip (DDH), Legg-Calvé-Perthes disease (LCPD), slipped capital femoral epiphysis (SCFE) and hip joint infections are the most common cause of juvenile hip osteoarthritis (JHOA) [2]. The complex management and the catastrophic consequences of these conditions justify the active research interest in this field [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%